Abolishing Child Marriage in Indonesia’s Marriage Law through Feminist Legal Theory and Child’s Rights Approach - Sigiro, Atnike Nova (Yayasan Jurnal Perempuan, 2020)
The Law No. 1 year of 1974 on Marriage Law had set the minimum age for marriage of 16 years old for women and 19 years old for men. This minimum age for setting up marriage is not only a form of legalization for conducting child marriage, but also a form of legalized gender-based discrimination, particularly against girls. In 2019, the Law was finally revised thus the discriminating set of minimumage for marriage was abolished, and the minimum age was set into 19 years old for both women and men. Koalisi 18+ is a civil society network in Indonesia, which work to abolish legalized child marriage through the revision of Marriage Law. They work through judicial review of the Marriage Law at the Constitutional Court, and also through encouraging revision of the Marriage Law at the parliament(DPR). This article describes and analyze the key discourses appeared during the effort to abolish and revise the Marriage Law No.1 Year 1974 through child’s rights and feminist legal approaches.